Journeying Through a Pedagogy of Peace: Creating and Translating an Indigenous Critical Pedagogical Framework from Theory to Practice - Brant, Lindsay Marie (2024)
The COVID-19 pandemic in March 2020 not only disrupted the world but also sparked a profound period of reflection for me. It became clear that my core values and beliefs, particularly as they relate to teaching and learning, needed a significant shift. The pandemic forced us to reconsider how we live, work, and interact with one another, highlighting the inadequacies of existing systems. For me, it ignited an urgency to create new ways of relating to myself, others, and the world. This deep introspection—combined with ceremony, writing, and dreaming—laid the foundation for a transformative journey grounded in my Haudenosaunee language, culture, and worldview. Journeying Through a Pedagogy of Peace: Creating and Translating an Indigenous Pedagogical Framework from Theory to Practice is a portfolio-based PhD that works at the intersection of poetry, writing, values, ethics, and theory. It moves beyond reflection to intentional action, challenging the outdated Western educational models still rooted in industrial modes of production, consumption, and exclusion. These structures must be reimagined if we are to survive and thrive as a global society. In this PhD, I critically examine Indigenization and decolonization, drawing on both my lived experiences and key works in education, cultural studies, and Indigenous studies. My approach is deeply grounded in the land, worldviews, and knowledge systems of the Haudenosaunee and Anishinaabe peoples of Katarokwi/Kingston. Centering "place" is not just a methodological choice; it is essential to ensure that Indigenous perspectives, rooted in land, language, kinship, and relationality, shape how we transform education. The work I present is not just a personal or academic exercise; it is a call to action. Western educational paradigms must adapt to include Indigenous knowledge systems, or risk perpetuating structures of exclusion and inequity. By embedding Indigenous methodologies into education, we not only enrich learning environments but also create a path toward a more ...